The science case for the EISCAT_3D radar - McCrea, Ian; Aikio, Anita; Alfonsi, Lucilla; Belova, Evgenia; Buchert, Stephan; Clilverd, Mark; Engler, Norbert; Gustavsson, Björn; Heinselman, Craig; Kero, Johan; Kosch, Mike; Lamy, Hervé; et al. (Progress in Earth and Planetary Science, 2015)
The EISCAT (European Incoherent SCATer) Scientific Association has provided versatile incoherent scatter (IS) radar facilities on the mainland of northern Scandinavia (the EISCAT UHF and VHF radar systems) and on Svalbard (the electronically scanning radar ESR (EISCAT Svalbard Radar) for studies of the high-latitude ionised upper atmosphere (the ionosphere). The mainland radars were constructed about 30 years ago, based on technological solutions of that time. The science drivers of today, however, require a more flexible instrument, which allows measurements to be made from the troposphere to the topside ionosphere and gives the measured parameters in three dimensions, not just along a single radar beam. The possibility for continuous operation is also an essential feature. To facilitatefuture science work with a world-leading IS radar facility, planning of a new radar system started first with an EU-funded Design Study (2005–2009) and has continued with a follow-up EU FP7 EISCAT_3D Preparatory Phase project (2010–2014).